Determination of factors associated with physical activity levels among adolescents attending school in Kuantan, Malaysia. - Dan, S.P.; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir (Nutrition Society of Malaysia, 2011)
Introduction: Findings from the National Health and Morbidity Survey III (MOH, 2008) indicate a 43.7% prevalence of physical inactivity among Malaysian adults. This sedentary lifestyle can also be observed among children and adolescents. Methodology: A cross-sectional study was conducted to determine factors associated with physical activity levels of four hundred, 13 year-old adolescents in Kuantan, Pahang. Data on socio-demographic, health-related, and psychosocial factors were collected using a self-administered questionnaire while physical activity level was assessed using the Physical Activity Questionnaire for Older Children (PAQ-C). Results: About one-third of the respondents were in the low physical activity level category, 61.5% were in the moderate category and only 3.0% of the adolescents were in the high physical activity level category. Males were more physically active than females (χ 2=23.667, p=0.0001) with female adolescents (45.1%) twice as likely as male adolescents (22.1%) to be in the low physical activity level category. The associations between physical activity level with socio-demographic and health-related factors, perception of weight status and body parts satisfaction were not significant. However, physical activity was found to be positively correlated with physical activity self-efficacy (r=0.496, p=0.0001), peer influence (r=0.468, p=0.0001), family influence (r=0.298, p=0.0001) and beliefs in physical activity outcomes (r=0.207, p=0.0001). Negative relationships were found between physical activity with depression (r=-0.116, p=0.021) and body size discrepancy (r=-0.143, p<0.01). Respondents who had a better perception of their current health status were more physically active (χ 2=21.062, p=0.0001). Multivariate analyses for the prediction of physical activity showed that physical activity self-efficacy, sex and peer influence were the most significant contributors in explaining physical activity among adolescents. Conclusion: Physical activity interventions should include psychosocial components as mediator variables in interventions designed to promote regular physical activity in adolescence.